Effect of home training during the COVID-19 lockdown on physical performance and perceptual responses of team-sport athletes: a mini-review - Paludo, Ana; Karpinski, Kathleen; Silva, Shauane; Kumstát, Michal; Sajdlová, Zuzana; Milanovic, Zoran (Biology of Sport, 2022)
This article aims to summarize the effects of home training performed during the COVID-19 lockdown on physical performance and perceptual responses among team-sport athletes. Studies with comparison of pre-post lockdown results of physical performance and perceptual responses were considered. A search was made in PubMed and SPORTDiscus databases. The PICO criteria were used for the keywords “athlete” AND “home-based training” AND “performance” OR “mental health”, with their respective entry terms. The multistage process of selection followed the PRISMA 2020 recommendations. Of 586 records identified, 9 articles were available for the final process. Physical performance was evaluated for 8 studies with the VO2max change ranging from 5.7% to -9%; an increase in the duration of sprint test ranging from 0.4% to 36%; an increase of agility duration of 12.4%; a decrease in maximal repetition load of 2.9%; and changes in countermovement jump height ranging from -4.7% to +15.4% after home training. Regarding the perceptual responses, no significant changes in wellbeing and mental index and a significant decrease in motivation and perceived effort were reported during the home training in lockdown. Based on the articles selected, home training programmes performed by athletes from team sports during the COVID-19 lockdown presented inconsistent results in physical performance, decreasing by up to 36%, and maintaining the wellbeing and mental index, but with a significant drop in training motivation and perceived effort. Caution should be taken considering the small number of articles included in the study.